The Circadian Clock Gene Csnk1e Regulates Rapid Eye Movement Sleep Amount, and Nonrapid Eye Movement Sleep Architecture in Mice - Zhou, Lili (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: Efforts to identify the genetic basis of mammalian sleep have included quantitative trait locus (QTL) mapping and gene targeting of known core circadian clock genes. We combined three different genetic approaches to identify and test a positional candidate sleep gene — the circadian gene casein kinase 1 epsilon (Csnk1e), which is located in a QTL we identified for rapid eye movement (REM) sleep on chromosome 15. MEASUREMENTS AND RESULTS: Using electroencephalographic (EEG) and electromyographic (EMG) recordings, baseline sleep was examined in a 12-h light:12-h dark (LD 12:12) cycle in mice of seven genotypes, including Csnk1e(tau/tau) and Csnk1e(-/-) mutant mice, Csnk1e(B6.D2) and Csnk1e(D2.B6) congenic mice, and their respective wild-type littermate control mice. Additionally, Csnk1e(tau/tau) and wild-type mice were examined in constant darkness (DD). Csnk1e(tau/tau) mutant mice and both Csnk1e(B6.D2) and Csnk1e(D2.B6) congenic mice showed significantly higher proportion of sleep time spent in REM sleep during the dark period than wild-type controls — the original phenotype for which the QTL on chromosome 15 was identified. This phenotype persisted in Csnk1e(tau/tau) mice while under free-running DD conditions. Other sleep phenotypes observed in Csnk1e(tau/tau) mice and congenics included a decreased number of bouts of nonrapid eye movement (NREM) sleep and an increased average NREM sleep bout duration. CONCLUSIONS: These results demonstrate a role for Csnk1e in regulating not only the timing of sleep, but also the REM sleep amount and NREM sleep architecture, and support Csnk1e as a causal gene in the sleep QTL on chromosome 15. CITATION: Zhou L; Bryant CD; Loudon A; Palmer AA; Vitaterna MH; Turek FW. The circadian clock gene Csnk1e regulates rapid eye movement sleep amount, and nonrapid eye movement sleep architecture in mice. SLEEP 2014;37(4):785-793.